2019
DOI: 10.14221/ajte.2019v44n10.2
|View full text |Cite
|
Sign up to set email alerts
|

How Do Teacher Affective and Cognitive Self-Concepts Predict How Do Teacher Affective and Cognitive Self-Concepts Predict Their Willingness to Teach Challenging Students? Their Willingness to Teach Challenging Students?

Abstract: Building on and extending earlier research on student selfconcepts and studies investigating teachers working with students with social, emotional, or behavioural difficulties, disorders, or disturbance, this longitudinal study examined teacher self-concepts in relation to their willingness to teach challenging students in mainstream classrooms. In the current study, "challenging students" refer to those who may pose a challenge to the teacher, either behaviourally or academically. Statistical measures include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Both self-concept and self-efficacy are self-perceptions and are a result of individual cognitive appraisal [28]. A person's self-perceived competence and confidence may or may not correspond to the person's actual competence, but regardless, they influence "behavioural, affective, and cognitive outcomes" [29] (p. 21) [30]. Bandura [31] stated that "beliefs of personal efficacy constitute the key factor of human agency.…”
Section: Introductionmentioning
confidence: 99%
“…Both self-concept and self-efficacy are self-perceptions and are a result of individual cognitive appraisal [28]. A person's self-perceived competence and confidence may or may not correspond to the person's actual competence, but regardless, they influence "behavioural, affective, and cognitive outcomes" [29] (p. 21) [30]. Bandura [31] stated that "beliefs of personal efficacy constitute the key factor of human agency.…”
Section: Introductionmentioning
confidence: 99%
“… Note : (1) is adapted from Thomas (2018) (b) is adopted from TIMSS (2015). (c) is adopted from Nwosu et al (2020) and Nwosu, Wahl, Oparaugo, et al (2021); Nwosu, Wahl, Cassim, et al (2021)) as developed by Low et al (2019) and Mahat (2008). ( α ) = Cronbach alpha.…”
Section: Methodsmentioning
confidence: 99%
“…Teacher willingness to include children with special needs questionnaire (TWICWSNQ) This is a 10-item questionnaire that measures the willing efforts and intentions of regular teachers to accept SEN. Nwosu et al (2020) and Nwosu, Wahl, Oparaugo, et al (2021); Nwosu, Wahl, Cassim, et al (2021) reported that this questionnaire is a combination of the 'Teacher Willingness to Teach Challenging Children Questionnaire (TWTCCQ)' developed by Low et al (2019) and the 'Teachers' Multidimensional Attitude towards Inclusive Education Scale (TMATIES)' developed by Mahat (2008). They reported that the essence of this merger is the understanding that teaching SEN also demands provision of emotional support to these students.…”
Section: Teacher Job Satisfaction Scale (Tjs)mentioning
confidence: 99%
See 2 more Smart Citations